FAKTOR PENYEBAB RENDAHNYA MINAT SISWA KELAS VIII DALAM MEMANFAATKAN LAYANAN KONSELING PERORANGAN - Miranti Miranti; Yuline Yuline; Amallia Putri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The goal of this study is to determine why SMP Negeri 2 Sungai Raya's eighth-grade students show such little interest in using the individualcounseling services that are offered there. For the conducted study, the descriptive approach is linked with a quantitative strategy in the formof survey research. Eighty students made up the study's total population, and the entire population served as the study's sample. Indirect communication techniques, such as surveys delivered via links to Google forms, were utilized by the researchers to gather data. Percentage correction was also used to assess the outcomes of the study's participants. Results revealed that internal factors contributed to students' lack of interest in using individual counseling services,which led to results in the medium category of 56 percent, while external factors contributed to students' lack of interest in using individual counseling services, which led to results in the medium category of 55 percent. The percentage of students who used individual counseling services was 54 percent in the medium category when it came to the topic of whether guidance teachers and counseling encourage students to do so. According to the summary above, thereare a number of issues that prevent students from receiving individual counseling services at SMP Negeri 2 Sungai Raya.